Comparative Analysis of the Exposure and Surgical Freedom of the Endoscopic Extended Minipterional Craniotomy and the Transorbital Endoscopic Approach to the Anterior and Middle Cranial Fossae. Issue 2 (14th December 2018) - Noiphithak, Raywat; Yanez-Siller, Juan C; Revuelta Barbero, Juan M; Cho, Raymond I; Otto, Bradley A; Carrau, Ricardo L; Prevedello, Daniel M
Abstract: BACKGROUND: Numerous minimally invasive approaches to the skull base have been successively developed. Knowledge of the surgical nuances of a specific approach may facilitate approach selection. This study sought to compare the nuances of an extended version of the minipterional craniotomy (EMPT) with those of the transorbital endoscopic approach (TOEA) to the anterior and middle cranial fossae (ACF and MCF, respectively). OBJECTIVE: To quantitatively analyze and compare the area of exposure and surgical freedom between EMPT and TOEA to the ACF and MCF. METHODS: EMPT and TOEA were carried out in 5 latex-injected cadaveric heads, bilaterally (10 sides). For each approach, the area of exposure, surgical freedom, and angle of attack were obtained with neuronavigation and statistically compared. RESULTS: No significant difference was found between the mean area of exposure of EMPT and TOEA at the ACF and MCF ( P  = .709 and .317, respectively). The mean exposure area at the ACF was of 13.4 ± 2.6 cm 2 (mean ± standard deviation) and 13.0 ± 1.9 cm 2 for EMPT and TOEA, respectively. Except for the crista galli, EMPT afforded a larger area of surgical freedom at all targets. EMPT also achieved significantly greater attack angles in vertical axis except to the crista galli. The horizontal attack angles to all targets were similar between approaches. CONCLUSION: EMPT and TOEA offer a comparable area of exposure at the ACF and MCF in the cadaver; however, the instrument maneuverability afforded by EMPT is superior. Further studies are necessary to better define their precise surgical application.